Telomemore enables single-cell analysis of cell cycle and chromatin condensation - Yakovenko, Iryna; Mihai, Ionut Sebastian; Selinger, Martin; Rosenbaum, William; Dernstedt, Andy; Gröning, Remigius; Trygg, Johan; Carroll, Laura; Forsell, Mattias; Henriksson, Johan (Nucleic acids research, 2025)
Single-cell RNA-seq methods can be used to delineate cell types and states at unprecedented resolution but do little to explain why certain genes are expressed. Single-cell ATAC-seq and multiome (ATAC + RNA) have emerged to give a complementary view of the cell state. It is however unclear what additional information can be extracted from ATAC-seq data besides transcription factor binding sites. Here, we show that ATAC-seq telomere-like reads counter-inituively cannot be used to infer telomere length, as they mostly originate from the subtelomere, but can be used as a biomarker for chromatin condensation. Using long-read sequencing, we further show that modern hyperactive Tn5 does not duplicate 9 bp of its target sequence, contrary to common belief. We provide a new tool, Telomemore, which can quantify nonaligning subtelomeric reads. By analyzing several public datasets and generating new multiome fibroblast and B-cell atlases, we show how this new readout can aid single-cell data interpretation. We show how drivers of condensation processes can be inferred, and how it complements common RNA-seq-based cell cycle inference, which fails for monocytes. Telomemore-based analysis of the condensation state is thus a valuable complement to the single-cell analysis toolbox.
Keywords: Chromatin Immunoprecipitation Sequencing; lidé; RNA-Seq; fibroblasty; Chromatin; B-lymfocyty; buněčný cyklus; Cell Cycle; telomery; Humans; analýza jednotlivých buněk; Binding Sites; chromatin; sekvenování transkriptomu; Single-Cell Analysis; B-Lymphocytes; Fibroblasts; Telomere; vazebná místa; ChiP sekvenování